SPIRITUAL INTELLEGENCE - R, Ramdani (JURNAL DIMENSI, 2016)
The ability of understanding mathematical concepts and was a math learning goals stated by the Ministry of Education, and was a very important aspect in learning mathematics. Lack of understanding of mathematical concepts students will affect the quality of student learning that result in low student achievement in school, it was also happening in SMP N Lembah Gumanti. Think Talk Write learning strategies was one alternative to improve the liveliness and creativity of students in learning.This research is a Quasi Experiment. The population in this study were students of SMP N Lembah Gumanti District. The samples in this study were students of class VIII 1 SMP N 3 Lembah Gumanti as experimental class and VIII 2 grade students as a class randomly selected controls. Instrument used was a written test. The data obtained were analyzed using ANCOVA test (analysis of Covariance).The results showed that the ability of understanding the overall concept and capable students who are taught by low initial learning strategy TTW higher than students taught with conventional learning.